Peran Serangga Tanah dalam Budidaya Talas Beneng di Karangtanjung - Ilham Reza Ferdiansyah; Nuniek Hermita; Andi Apriany Fatmawaty; Andree Saylendra (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Araceae is a plant family known as taro with a high level of diversity and is easily found by the public. Beneng taro (Xanthosoma undipes) is a plant in the Araceae family that is included in the local food commodities originating from Banten Province, especially in the Mount Karang. Soil insects are a type of insects that have an essential role in the food cycle, which supports the weathering process of organic material to have a positive influence on the physical and chemical properties of soil. The diversity of soil insects on taro beneng plants in Cinyurup Village is essential to be known to open up new opportunities for understanding their ecological benefits related to agricultural sustainability and biodiversity conservation. This research aims to determine soil insects and their role in the beneng taro cultivation area and to determine the diversity index of soil insects in the area. This research was carried out in February-March in Cinyurup Village, Karang Tanjung District, Pandeglang Regency. This research includes quantitative descriptive research with an exploratory method. Sampling was carried out by purposive sampling using the pitfall trap technique. The samples in this research are all ground insects trapped in pitfall traps. Trapped samples were identified based on their role and the calculated diversity index of the Shannon-Wiener method, which can facilitate the analysis of information about the type of individual and the number in an area. The identification results showed that there were 252 insects belonging to 6 families, namely Formicidae, Gryllidae, Tetrigidae, Scarabaeidae, Anisolabidae, and Muscidae. Formicidae and Scarabaeidae are land insects found in abundance due to the farming system based on the cultivation of wire that supports their survival. The diversity index value was obtained at 1.03064 which is included in the medium category. The insects found have varied roles, namely predators (Formicidae, Anisolabidae), herbivores (Gryllidae, Tetrigidae), pollinators (Formicidae, Muscidae), and decomposers (Scarabaeidae).